(untitled) (EAAE Annual Conference Proceedings, 2025)
This paper presents a methodological inquiry into the creative use of archival materials in architectural education, focusing on their potential as both sources of inspiration and visually operative tools in design processes. Using a one-week student workshop titled Belt. Gate. Narrate., held in Cracow, Poland, as a case study, the paper explores how narrative design can serve as a framework for engaging with historical documents – particularly maps – to generate site-specific, time-sensitive architectural proposals. The workshop centred on Planty Park, a 4-kilometer green belt that encircles Cracow’s Old Town, where medieval fortifications once stood. Rather than treating the park as a neutral perimeter, the methodology recognised it as a transformative and liminal space – a layered urban threshold between the historical core and the city’s later expansions. This in-between condition, both spatial and temporal, positioned the park as a fertile site for narrative interpretation, one charged with historical memory, ambiguity, and potential. At the core of the pedagogical approach was the superimposition of archival and contemporary maps, used not simply as references but as design catalysts. These layered cartographies invited students to read the city as a palimpsest, where traces of the past can be reactivated to shape new spatial narratives. Through this technique, archival material became a generative device – capable of revealing hidden continuities, ruptures, and moments of transformation. Students responded with high-quality conceptual urban and architectural intervention projects that unfolded as multimodal narratives – visual “stories,” large-format anecdotal drawings, and short interpretive videos – combining analogue and digital media, hand-drawn and AI-generated imagery. The plurality of formats encouraged poetic, open-ended expressions, allowing for deeply personal interpretations of site, history, and transition. This paper argues for a methodological shift from archives as static repositories to active instruments in design pedagogy. By recontextualising historical documents through narrative strategies and situating them within liminal urban conditions, such as Planty Park, architectural education can cultivate new modes of spatial thinking – ones that are historically informed, critically imaginative, and emotionally resonant.